2013
DOI: 10.1021/la304485e
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Ketals of Arjunolic Acid into Vesicles and Fibers Yielding Gel-Like Dispersions

Abstract: Ten aliphatic and aromatic ketals of arjunolic acid, a renewable, nanosized triterpenic acid which is obtainable from Terminalia arjuna, have been synthesized upon condensation with aldehydes. Self-assembly properties of the ketals have been studied in a wide range of organic liquids. With the exception of the p-nitrobenzylidene derivative, low concentrations of the ketals self-assemble and form gel-like dispersions in many of the organic liquids examined. The morphologies of the assemblies, studied at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…The fibrillar self‐asemblies observed by SEM might be due to increase in concentration of the gelators by solvent evaporation during xerogel formation. The transformation of fused vesicles to fibers at higher concentration and coexistence of vesicles along with a certain percentage fibers has also been reported in other systems ,…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The fibrillar self‐asemblies observed by SEM might be due to increase in concentration of the gelators by solvent evaporation during xerogel formation. The transformation of fused vesicles to fibers at higher concentration and coexistence of vesicles along with a certain percentage fibers has also been reported in other systems ,…”
Section: Resultssupporting
confidence: 63%
“…Among various supramolecular building blocks from natural resources, the pentacyclic triterpenoid molecules have gained a significant attention of the scientific community in recent years because these nano‐sized chiral triterpenoid molecules possess a rigid backbone along with different functional groups at different positions and orientations . Because of this structural uniqueness of these triterpenoid molecules, they can even self‐assemble without any structural modification yielding diversified self‐assembled structures like fibers,, vesicles,,,,, flowers,, etc. which have been exploited as drug delivery vehicle, dye removing agent, template for the synthesis of organic‐inorganic advanced hybrid material for using it as recyclable heterogeneous catalyst, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These were done by inverted test tube experiments after gels were stabilized in sealed test tubes for 1–2 h [15,4850]. It was observed that the thermal stability of these CT gels based on 3 and 4 increased with an increase in the total concentration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(Gupta et al 2011). During our investigations on the utilization of triterpenoids (C30s) as renewable functional nano-entities (Bag and Dash 2011;Bag and Paul 2012;Bag et al , 2013Majumdar 2012, 2014), it occurred to us that the medicinally important bark extract of Abroma augusta L., rich in polyphenolic compounds, can be utilized for the synthesis of AuNPs from HAuCl 4 (Mittal et al 2013). Herein, we report the experimental evidence for the presence of antioxidants including polyphenols in the bark extract of Abroma augusta L. and the use of the bark extract for a very mild, environment friendly and efficient synthesis of AuNPs without any additional capping or stabilizing agents.…”
Section: Introductionmentioning
confidence: 99%